Analgesic efficacy and safety of erector spinae plane block versus serratus anterior plane block in breast surgery—a meta-analysis and systematic review of randomized controlled trials - Samiullah Shaikh; Umm E Salma Shabbar Banatwala; Paranshi Desai; Muhammad Arham Khan; Rimsha Bint-e-Hina; Sidra Samad; Muhammad Hamza Sikandari; Ali Nawaz; Rana Ijaz; Shayan Asmat; Abeer Fatima; Harim Mirza; et al. (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Background Mastectomy and breast-conserving surgery are key interventions for breast cancer, a leading cause of cancer-related mortality in women. Many undergoing breast surgery experience postoperative pain compromising their functionality and quality of life. While multiple pain management strategies are available, evidence comparing the erector spinae (ESPB) and serratus anterior plane blocks (SAPB) for improving post-surgical pain management in breast cancer surgery patients is limited. Therefore, we investigated the efficacy and safety of these two regional anesthesia techniques. Methods After PROSPERO registration, we systematically searched PubMed, Google Scholar, and Cochrane Library until May 2024. Risk ratios (RR) were calculated for dichotomous outcomes and standard mean differences (SMD) or mean differences (MD) were computed for continuous data. RevMan Review Manager 5.4.1 was used for the data analysis and generation of forest plots as well as funnel plots. The Cochrane Risk of Bias tool 2.0 (18) and Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) guidelines were used to appraise and evaluate the evidence (19). Results A total of 9 randomized control trials enrolling 550 patients were included. Static pain scores at 0, 6, 8, 12, and 24 h after surgery, dynamic pain scores computed at 0, 8, 12, and 24 h after surgery and area under the curve (AUC) static pain score at all time points between 0 and 24 h (SMD (HKSJ 95% CI) − 0.27 [− 0.99, 0.45]) did not significantly vary with either plane block. Postoperative morphine consumption in the first 24 h and the number of patients requesting analgesia were significantly greater in those receiving SAPB [MD: − 1.41 (95% C.I. − 2.70, − 0.13), p = 0.03] and [RR: 1.28 (95% C.I. 1.00, 1.63), p = 0.05], respectively. The time to first postoperative analgesic use was significantly greater among those administered ESPB [MD: 1.55 h, (95% C.I. 1.02, 2.09), p < 0.01]. Patient satisfaction scores and the incidence of nausea and vomiting were similar across both groups. Conclusions While pain scores with either block are comparable, ESPB reduces postoperative morphine consumption and may be the favorable option in breast cancer patients undergoing surgery.